USE OF THE ART OF CONTRAST IN THE WORK OF "NAZM UL-JAVAHIR" - Khojaeva Shoirakhan Bakhtiyar kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted to the analysis of the essence, philosophical foundations of the art of tazad and its place in our classic literature, in particular, in Alisher Navoi’s "Nazm ul-Javahir". In it, the unique aspects and features of tazad art used in this work were researched and scientific conclusions were drawn.